The Lakes-to-the-Gulf Deep Waterway: I - Shelton, William A. (Journal of Political Economy, 1912)
Louis; the channel of the Mississippi River between St. Louis and the Gulf composes the remainder of the route. Beginning at Lake Michigan and the mouth of the Chicago River, in the very heart of the city of Chicago, the route follows the Chicago River for 6.25 miles from Lake Michigan to Robey Street, the Chicago Sani? tary and Ship Canal for 32.35 miles to the junction with the Des Plaines River and the Illinois and Michigan Canal at Joliet,1 the Des Plaines River for 15.73 miles to the junction of the Kankakee,2 the Illinois River for 273 miles to the Mississippi, and the Mississippi for 1,332 miles3 to the Gulf of Mexico.4 The total distance between Chicago